2004
DOI: 10.1590/s0102-311x2004000500024
|View full text |Cite
|
Sign up to set email alerts
|

Trabalho rural e intoxicações por agrotóxicos

Abstract: Pesticide use is intensive in Brazilian agriculture. Population-based

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
52

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 22 publications
(37 reference statements)
0
16
1
52
Order By: Relevance
“…In their own words, young people are hired at 17, but by 25 or 26 they are no longer able to keep on doing the job. Faria et al (2004) 16 tried to build a profile of pesticide exposure and analyze the incidence of poisoning by these products. Looking at a group of 1,379 farmers, they found that the incidence of pesticide poisoning was of 2.2 episodes for every one-hundred exposed workers; no differences were found in relation to gender.…”
Section: Vector Electronystagmography (Veng)mentioning
confidence: 99%
“…In their own words, young people are hired at 17, but by 25 or 26 they are no longer able to keep on doing the job. Faria et al (2004) 16 tried to build a profile of pesticide exposure and analyze the incidence of poisoning by these products. Looking at a group of 1,379 farmers, they found that the incidence of pesticide poisoning was of 2.2 episodes for every one-hundred exposed workers; no differences were found in relation to gender.…”
Section: Vector Electronystagmography (Veng)mentioning
confidence: 99%
“…No entanto, o uso de botas, avental, calça e camisa de mangas compridas e outros equipamentos de proteção individual, foram considerados menos importantes como medida de segurança. Resultados semelhantes foram relatados por Faria (2004) sobre os equipamentos mais específicos para proteção química, onde mais de 35% dos trabalhadores admitiram nunca usar luvas, máscaras ou roupas de proteção. No entanto, Garcia & Alves Filho (2005) citam uma série de dificuldades e limitações na abordagem estrita da questão dos EPI's nos trabalhos agrícolas, tais como: pouca disponibilidade de profissionais habilitados para atuar junto a serviços técnicos de prevenção no campo; visão geral equivocada e, socialmente, difundida no meio técnico sobre o alcance, a eficácia e a viabilidade técnica de indicações generalizadas de uso do EPI; a responsabilidade colocada ao engenheiro agrônomo na indicação de EPI (conforme estabelece a Lei dos Agrotóxicos), sendo que este profissional não tem formação específica para tal indicação.…”
Section: Resultsunclassified
“…The State and industrial stimulus to the intensive use of pesticides, associated with public policies for health, environment and labor based on the "safe use" paradigm, have been shown the increasing cases of acute [9][10][11][12][13][14][15][16][17][18] and chronic [19][20][21] intoxications, especially among family farmers.…”
Section: Introductionmentioning
confidence: 99%